2015
DOI: 10.4209/aaqr.2015.03.0176
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Control of Elemental Mercury/Sulfur Dioxide/Nitrogen Monoxide from Coal-Fired Flue Gases with Metal Oxide-Impregnated Activated Carbon

Abstract: This research investigated the effects of transition metal oxide impregnation on the physical/chemical properties and on the multipollutant (i.e., Hg 0 /SO 2 /NO) control of a commercial coconut shell-based activated carbon. V, Mn, and Cu oxides of 5 wt% as their precursor metal hydroxides were impregnated onto the activated carbon surface. After the transition metal oxide impregnation, the surface area and pore volume of activated carbon decreased. The surface morphology of activated carbons was similar prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Using porous materials, especially activated carbons as adsorbents, have been shown as profitable Hg 0 emission control approaches (Lin et al, 2015). The adsorptive efficiency of activated carbon largely depends on the surface and porous characteristics of activated carbon, including surface area, pore volume and size distribution, and surface functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Using porous materials, especially activated carbons as adsorbents, have been shown as profitable Hg 0 emission control approaches (Lin et al, 2015). The adsorptive efficiency of activated carbon largely depends on the surface and porous characteristics of activated carbon, including surface area, pore volume and size distribution, and surface functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Ce oxide has also been known to have a great oxygen storage capacity and outstanding redox characteristics and can be a promising additive for low-temperature NH 3 -SCR (Xu et al, 2018). Our earlier studies have also shown that activated carbon and zeolite impregnated with Cu oxide and Cu chloride had great Hg 0 adsorption performance (Chiu et al, 2014(Chiu et al, , 2015Tsai et al, 2017). Therefore, a combination of Cu-Mn or Cu-Mn-Ce oxides supported by porous materials, such as SiO 2 , could possess great effectiveness in NO reduction and Hg 0 oxidation followed by subsequent adsorption.…”
Section: Introductionmentioning
confidence: 94%
“…The average Hg 0 removal efficiency decreased with the increase of the temperature. The decrease in THg removal efficiency at 350°C was expected because the adsorption of Hg is thermodynamically unfavorable at elevated temperature (Chiu et al, 2015).…”
Section: Hg 0 Removal Test On Cu-mn and Cu-mn-ce Incorporatedmentioning
confidence: 99%
“…Therefore, to overcome these challenges, numerous vanadium-free catalysts have been studied, including noble-metal catalysts (Zahaf, 2015), M-zeolite catalysts (M-Fe, Cu, Mn, Mo) (Perezramirez, 2004;Yoshida, 2004;Liu et al, 2011a;Ochońska et al, 2012;Schuricht and Reschetilowski, 2012;Mejri et al, 2016) and metal oxide catalysts (Fe-based oxide catalysts, Mn-based oxide catalysts, Cu-based oxide catalysts, Cebased oxide catalysts, Cr-based oxide catalysts, etc.) (Kato et al, 1981;Yang et al, 1992;Duffy et al, 1994;Kapteijn et al, 1994;Chen et al, 1995;Schneider et al, 1995;Zhu et al, 2000;Eigenmann et al, 2006;Kang et al, 2007;Xu et al, 2008;Liu et al, 2013a;Chiu, 2015;Yu, 2015;Yu et al, 2017). Fe-based and Mn-based catalysts have been the most favorable catalysts among the various vanadium-free catalysts.…”
Section: Introductionmentioning
confidence: 99%